2020
DOI: 10.1186/s12894-020-00666-7
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of quality of life and satisfaction with life of patients before and after surgery of an isolated apical defect using synthetic materials

Abstract: Background: Pelvic floor static disorders constitute a significant clinical and social problem. The incidence of the problem increases with the age of female patients up to 80 years of age. Due to various methods of procedural treatment, eligibility for surgery should be carefully discussed with the patient. Ideally, the surgery should be effective and with the least possible number of complications. The objective of this study was to assess the quality of life of patients before and after the surgery of an is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Another study confirmed a significant improvement in the quality of life scores at 12 months [21]. Unfortunately, the study was not designed to assess anatomical outcomes.…”
Section: Discussionmentioning
confidence: 91%
“…Another study confirmed a significant improvement in the quality of life scores at 12 months [21]. Unfortunately, the study was not designed to assess anatomical outcomes.…”
Section: Discussionmentioning
confidence: 91%
“…There were two main procedures for vaginal surgeries: reconstructive (in two subgroups, including repair with natural tissue [ 17 , 19 , 20 , 23 , 24 , 31 , 36 , 37 , 38 , 60 , 61 , 63 , 64 , 65 , 66 ] ( Table 2 ) and repair with mesh [ 7 , 9 , 12 , 21 , 25 , 26 , 29 , 32 , 35 , 39 , 40 , 41 , 42 , 43 , 44 , 55 , 62 , 67 , 68 , 69 , 78 , 82 , 83 , 85 ]) ( Table 3 ) and obliterative surgeries [ 18 , 27 , 60 , 71 , 72 , 73 , 86 ] ( Table 4 ). In one study, obliterative surgery and sacrospinous fixation in older postmenopausal women were compared, and the QoL was better in the sacrospinous group [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study involved 60 patients and was more focused on the assessment of patients` satisfaction after the surgery. The authors concluded that in most patients, surgical treatment of isolated apical defects using BSC-mesh resulted in the elimination of bothersome symptoms and improvement of quality of life [ 23 ].…”
Section: Discussionmentioning
confidence: 99%